The place of aerial surveys in British wildfowl research - The alternative methods of population study - Anonymous, Anonymous (Wildfowl, 1957)
A basic requirement for programmes of conservation is a knowledge of the size and distribution of the animal populations concerned. The capture/recapture technique can estimate population size, but a general knowledge of distribution is implicit in the sampling process. The majority of duck populations and some of the geese can therefore only be studied by direct survey methods. The Wildfowl Trust has taken over (from the former Wildfowl Inquiry Committee) and expanded the Wildfowl Count Scheme of surveys from the ground in Britain. Under this organisation some 700 volunteers count the number of ducks and geese present on selected inland and coastal waters. This is done at monthly intervals throughout most of the year, on fixed dates. In North America, with its much greater expanses of sparsely populated country, the problem has been tackled for more than twenty years by the use of aerial survey methods. The American winter flocks of wildfowl have been subjected for many years to an extensive sample census regularly towards the close of the shooting season. In January 1957, 150 aircraft were used, flying a total of 85,615 miles. All the indications are that estimates of numbers in flocks of wildfowl made by skilled observers from aircraft are as accurate as those made from the ground. When visual observation is supplemented by high oblique or vertical photographs as a permanent record, the final accuracy will be greater.